PENERAPAN MODEL TGT BERBANTUAN MEDIA PADIDAS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA SD - Nadia, Sarifa; Riswari, Lovika Ardana; Fakhriyah, Fina (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
The lack of application of learning models and media makes students less active when participating in learning activities. The lack of student activity during learning activities makes students less able to understand the material, resulting in low students' mathematical concept understanding ability. The purpose of this study was to determine the difference in the average value of students' mathematical concept understanding ability before and after using the TGT model assisted by PADIDAS media. This study is a quantitative pre-experimental study with a one group pretest-posttest design. The study was conducted at SD 4 Troso with a sample of 30 fourth grade students. In this study, data collection techniques used tests, interviews, observations and documentation and data analysis techniques used normality tests and hypothesis tests with the Paired Sample T-Test test. The results of the Paired Sample T-Test test obtained a Sig. (2-tailed) value of 0.000 <0.05 so that Ha was accepted and Ho was rejected. From these results it can be concluded that there is a difference in the average value of understanding mathematical concepts before and after using the TGT model assisted by PADIDAS media.